KEKUATAN PEMBUKTIAN KETERANGAN SAKSI KORBAN ANAK DALAM TINDAK PIDANA PERSETUBUHAN OLEH ANAK - Muhammad Aulia Farhan (2021)
Abstract Witness testimony is an important factor in the implementation of a criminal court process, giving testimony is certainty given to judges in court about the event or something in dispute by giving oral testimony that is personally seen or heard directly. In the case of criminal acts related to children, the quality of evidence in providing testimony as a witness is very important. The strength of proof of testimony of child victim witnesses, which in carrying out evidence without being sworn in is additional evidence, the testimony of the witness who is not sworn in is not evidence, but if the testimony is in accordance with the testimony of the witness, then the information can be used as additional legal evidence. another. Forms of legal protection for children as witnesses in criminal cases include : physical, mental, and social safety guarantees; psychological protection in the form of assistance; children are free to choose a trusted companion; the testimony taking process was carried out in informal situations; the existence of a special child official in the judicial process; legal aid to children. Keywords: Witness Information, Child Intercourse, Legal Protection